Changing referents : learning across space and time in China and the West - Jenco, Leigh K., 1977- (Oxford University Press, 2015)
Even as globalisation has exposed the Eurocentric character of the academic theories used to understand the world, most scholarship continues to rely on the same parochial vocabulary it critiques. Against those who insist our thinking cannot escape the dominant terms of Euro-American modernity, this book shows how methods for understanding cultural others can take theoretical guidance from those very bodies of thought typically excluded by political and social theory.